APPLICATION OF VISUAL REPELLENTS IN BIRD CONTROL - Matsyura, A. V.; Yakovlev, R. V.; Ulanov, P. N. (Acta Biologica Sibirica, 2016)
Position of Barnaul municipal landfill at a distance of 6.3 km from the aerodrome is a violation of the requirements of the Federal Rules of Russian airspace. Site location and the birds’ presence at this point could cause a serious threat to the aircraft, as the vast majority of feed bird flights were registered at low altitude - less than 100 m. It was marked increase in the level of aircraft collisions with birds since 2011 in the vicinity of Barnaul airport area. Thus, the problem of bird management in the area of Barnaul landfill becomes crucial. The suggested repellents can reduce the number of birds in the area of solid waste landfill by 60-70% at a cost not exceeding 100,000 rubles for the technical equipment of the landfill by visual means of bird scaring during the breeding period (mass concentration of birds in landfill area). To improve the situation, it is advisable to install on the territory of waste sites several poles (height of about 4-5 m) with 10-12 special colored balls with a pattern of predator eyes and poles (height of about 5-6 m) with 8-10 special visual repellents - kites, providing strong bird repellent effects.